Differentiation of embryonic stem cells through controlled release of growth factors from microspheres - olaye, eghosa omoregie andrew/ E A O (2009)
The development of microspheres for the sustained delivery of protein and small drug delivery has been utilised in tissue engineering and drug delivery applications. However problems exist in obtaining a controlled and predictable release pattern of the encapsulated molecules from these materials. In this study, microspheres with a zero order release kinetic profile and no lag phase were developed from a novel PLGA based polymer blend.